COMPARATIVE ANALYSIS OF THE MERDEKA CURRICULUM AND DEEP LEARNING IN ISLAMIC EDUCATION AND CHARACTER EDUCATION AT SMP - Karima, Naila; Wirdati, Wirdati (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study investigates the comparative effectiveness of the Merdeka Curriculum and the Deep Learning approach (Mindful, Meaningful, Joyful Learning) in the teaching of Islamic Religious Education (PAI) and Character Education (BP) at SMPN 1 and SMPN 2 Sungai Beremas. The comparison is significant in understanding how different pedagogical orientations within the same national curriculum framework influence learning outcomes, instructional practices, and student engagement. Using a mixed-methods design, the study involved 245 students and 12 key informants. Quantitative analysis revealed a statistically significant difference between the two schools (p-value 0.015 < 0.05), with SMPN 2 achieving a higher and more homogeneous average score. In contrast, qualitative findings provided deeper insight into the contextual factors behind these results. SMPN 1 demonstrated strengths in leveraging digital infrastructure to support learning, whereas SMPN 2 exhibited strong pedagogical resilience by applying a contextual approach rooted in local wisdom to address limited facilities. Furthermore, the study identified limited instructional time allocation (3 hours per week) as the primary inhibiting factor, particularly affecting the effectiveness of the tahfiz program and the implementation of Problem-Based Learning methods. Overall, the findings suggest that the effectiveness of Deep Learning is shaped more by the quality of instructional interaction and teacher creativity than by the availability of physical facilities.